2013
DOI: 10.3109/09286586.2013.783082
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Refractive Error and Spectacle Coverage in Zoba Ma’ekel Eritrea: A Rapid Assessment of Refractive Error

Abstract: The study provides helpful findings to assist with the development of appropriate refractive service planning in Zoba Ma'ekel. Uncorrected refractive error is of public health importance and prompt measures are needed to address the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 8 publications
4
50
6
Order By: Relevance
“…The prevalence of refractive error was significantly higher among male participants compared to females (p = 0.02). Other related studies in Africa (Eritrea, Ghana, Uganda and Tanzania) 17 also demonstrated that refractive error is associated with increasing age and female gender.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The prevalence of refractive error was significantly higher among male participants compared to females (p = 0.02). Other related studies in Africa (Eritrea, Ghana, Uganda and Tanzania) 17 also demonstrated that refractive error is associated with increasing age and female gender.…”
Section: Discussionmentioning
confidence: 67%
“…The results of this study indicated a lower prevalence compared with similar RARE studies conducted in other African countries in people over the age of 15 years. For example, the prevalence of uncorrected refractive errors was reported as 6.4 per cent (95 per cent CI 5.6–7.2) in Eritrea, 8.6 per cent (95 per cent CI 7.7–9.6) in Uganda and 10.4 per cent (95 per cent CI 9.4–11.4) in Tanzania; however, the variability in the age cohorts prevents a direct comparison. For example, the Eritrean, Ugandan and Tanzanian RARE studies included people aged between 15 and 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited comparative studies for Tanzania due to methodology differences but studies conducted using similar rapid assessment methods in Eritrea, Mozambique (J Loughman, personal communication) and India reported lower prevalences of uncorrected refractive error, which were 6.4, 2.6 and 4.8 per cent, respectively. Studies conducted in Eritrea and Andhra Pradesh also showed higher spectacle use compared to our study …”
Section: Discussionmentioning
confidence: 99%
“…The Kahama district located in the Shinyanga region in Tanzania was chosen for this study due to its similarities in terms of socioeconomic status to the general population in Tanzania . The estimated population of Kahama in 2002 was 596,456 and the study population consisted of subjects aged 15 years and older.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation